MEDICAL PROMOTION EFFECT OF PHYSICAL EXERCISE ON PARKINSON'S DISEASE - Liu,Hui (2021)
ABSTRACT Introduction: Parkinson's disease is a common neurodegenerative disease in middle-aged and older people. Some studies have shown that sports can reduce its impact on physical functions. Objective: Based on the abovementioned research background, this paper explores the effect of moderate physical exercise on muscle tone and body posture of patients with Parkinson's disease. Methods: The article selected 72 Parkinson patients admitted to our hospital's Parkinson's Medical Center from 2019 to 2020. These were divided into a basic drug treatment group and a sports intervention group. The Ashworth score, walking speed, walking cycle, and walking distance of the two groups were recorded. At the same time, we performed statistical data analysis on the two sets of data obtained. Results: Compared with the basic treatment group, the modified Ashworth score of the sports intervention group decreased after treatment (P<0.01). The walking speed of the sports intervention group increased, the walking cycle was shortened, and the distance of repeated steps increased (P<0.01). Conclusion: Appropriate physical exercise can reduce muscle tone in patients with Parkinson's disease. It helps them increase their pace and improve small gait symptoms. Sports can help Parkinson patients adjust their body posture and promote their clinical treatment. Level of evidence II; Therapeutic studies - investigation of treatment results.